2021
DOI: 10.11648/j.avs.20210903.14
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-intestinal Tract Nematodes of Small Ruminants: Prevalence and Their Identification in and Around Alage, Southern Ethiopia

Abstract: A cross sectional study was conducted in small ruminants kept under extensive management system in and around Alage Agricultural Technical Vocational Educational and Training (ATVET) College from October to May, 2018/19. The objectives were set to estimate the prevalence and types of recovered parasites at genus level and assessment of their association with the animal risk factors. A total of 310 randomly collected fecal samples of small ruminants (206 goats and 104 sheep) were examined by simple floatation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…10.4%, Trichostrongles 6.5%, Nematodirus 6%, Oesophagostomum 5.5% and Trichuris Spp. 1.87% which agrees with genera reported from Eastern and Southeastern Ethiopia by ( Belina et al, 2017 ; Moje et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…10.4%, Trichostrongles 6.5%, Nematodirus 6%, Oesophagostomum 5.5% and Trichuris Spp. 1.87% which agrees with genera reported from Eastern and Southeastern Ethiopia by ( Belina et al, 2017 ; Moje et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The current study found that the overall prevalence of GINs in goats in the study area was 54.17%, which agrees with prevalence reports of 52.67% from Hararghe, eastern Ethiopia ( Belina et al, 2017 ) and 53.29% from Haramaya, eastern Ethiopia ( Ahmed et al, 2017 ). However, it is comparatively lower than prevalence reports of 78.2% from Alage, Southern Ethiopia ( Moje et al, 2021 ) and 100% nematode prevalence in goats from Nyagatare district, Rwanda ( Tumusiime et al, 2022 ). Similarly, the current study disagrees with prevalence reports of 42.1% in Tullo district, western Hararghe, Ethiopia ( Getachew et al, 2017 ) and 26.6% of GINs prevalence in goats from Damaturu, Yobe State, Nigeria ( Adamu and Kyari, 2023 ).…”
Section: Discussionmentioning
confidence: 65%
“…e results of this study corroborate with those previous studies done Abdi-Soojeede (2018) that showed a high prevalence of parasitic infections in goats with a percentage of 72.1%). e current nding was slightly lower than that previous studies conducted in di erent areas of Ethiopia, such as 78.2% in Alage (Moje et al, 2021), 76.3% in Central Ethiopia (Moti, 2008), and 82% in Genchi District (Emiru et al, 2013). e current nding, however, was signi cantly lower than those of 86.7% (Mideksa et al, 2016) and 85.22% (Pathak and Pal, 2008) from Ethiopia and India, respectively.…”
Section: Discussioncontrasting
confidence: 76%
“…This study revealed that the prevalence of gastrointestinal (GI) parasites small ruminates were 77.88%, and 70.28% in sheep and goats, respectively. These results were markedly lower than with the results of (11,(15)(16)(17)(18)(19)(20)(21)(22)(23). They have reported a prevalence of 96.38 % in goats of Ogaden rangelands, 90.41% and 82.13% in sheep and goats in and around Wolayita Sodo, 88.1% and 84.32% in sheep and goats in and around Mekele, 91.43% in sheep in and around Kombolcha, 90.94% and 94.85% in sheep and goats of Gonder, 100% in Boer goats at Adami Tulu agricultural research center 92.23% and 94.1% in sheep and goats of Mendayo district of Bale, 93.22% and 92.24% in sheep and goats of four Awrajas of Eastern Shoa, 90.23% and 88.33% in sheep and goats of Buno province and 85.79% in sheep in and around Asella respectively.…”
Section: Discussioncontrasting
confidence: 59%